2015
DOI: 10.5897/ajar2015.9342
|View full text |Cite
|
Sign up to set email alerts
|

Influence of harvest time in accumulation of biomass between cassava cultivars

Abstract: Lack of cultivar adapted to the planting area, as the ideal harvest period undertakes the productive potential of cassava. The study was conducted to evaluate the influence of different harvest seasons on total production of fresh and dry weight of four cassava cultivars. The used cultivars were: Branca de Santa Catarina (BSC), IAC 13, IAC 14-18 and Fiber that they were planted on 09/20/11 at the headquarters of the Regional Center Valley Paranapanema Paulista Agency for Agribusiness Technology (APTA), in Assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…This finding corroborates the analogous observations of Adetoro et al [35]; Eyinla et al [36] and Enesi et al [37] from separate researches on cassava. The dry matter content of cassava varieties evaluated in this study contradicts the observation of De Oliveira et al [38] who reported significantly comparable dry matter content for four cassava varieties they evaluated in their study. This discrepancy may not be unconnected to difference in cassava varieties evaluated in the two studies.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding corroborates the analogous observations of Adetoro et al [35]; Eyinla et al [36] and Enesi et al [37] from separate researches on cassava. The dry matter content of cassava varieties evaluated in this study contradicts the observation of De Oliveira et al [38] who reported significantly comparable dry matter content for four cassava varieties they evaluated in their study. This discrepancy may not be unconnected to difference in cassava varieties evaluated in the two studies.…”
Section: Discussioncontrasting
confidence: 99%